The Role of Karang Taruna in Overcoming Adolescent Behavioral Deviations in Globalization Era - Alfiyah, Reni; Prajanti, Sucihatiningsih Dian Wisika; Alimi, Moh Yasir (JESS (Journal of Educational Social Studies), 2019)
Deviations in adolescent behavior disrupt the upholding of social systems, cultural values, norms, rules and customs existing in society. The aims of the studies is to analyze the role of Karang Taruna in overcoming adolescent behavioral deviations in Somogede Village. The focus of the study covered the forms and causes of adolescent behavioral deviations and ways of adolescent coaching conducted by Karang Taruna of Somogede Village. The research approach used qualitative-phenomenology. The data collection was carried out by interviewing informants of teenagers, Karang Taruna coaches, village officials, parents and community leaders, Observation of the socio-cultural environment and document studies. The results showed that forms of adolescent behavioral deviations who violated social values and norms such as smoking, drinking and drug consuming, watching pornographic content, unhealthy dating, cursing and not respecting older people, while delinquency that was breaking the law such as the use of underage vehicles. The causes of adolescent deviations were from peer relationships, imperfect socialization, deviant subculture, poor parental, parental supervision and technological development and modernization. The role of Karang Taruna was played by giving youth coaching activities aimed at becoming good community members. The research conclusion explain that deviation violates the social values and law. The role of Karang Taruna is giving guidance and training in sport and social fields. The new finding behind globalization’s adolescent deviation is the use of technology among peers. The objectives of this study can be used as social controller through handling deviant behavior of teenager.